2003
DOI: 10.1051/0004-6361:20030722
|View full text |Cite
|
Sign up to set email alerts
|

H2absorption in a dense interstellar filament in the Milky Way halo

Abstract: Abstract. We investigate interstellar absorption from molecular hydrogen (H 2 ) and metals in an intermediate-velocity cloud (IVC) in the direction of the LMC star Sk -68 80 (HD 36521), based on data from the Far Ultraviolet Spectroscopic Explorer (FUSE) satellite. H 2 absorption from the Lyman and Werner bands is detected in 30 lines at radial velocities v LSR ≈ +50 km s −1 in this IVC that is presumably located in the Milky Way halo. We obtain a total logarithmic H 2 column density of log N(H 2 ) = 16.6 ± 0.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
3
1

Relationship

4
5

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 40 publications
3
37
1
Order By: Relevance
“…De Boer et al (1980 found UV absorption at 20 km s −1 (Galactic) and at 220, 250 and 290 km s −1 towards the LMC and proposed that the 220 km s −1 component might originate in coronal gas associated with the LMC. Intermediateand high-velocity clouds floating in the Galactic Halo have also been seen in front of the LMC at 60 and 120 km s −1 , interestingly also in H 2 absorption (Richter et al 1999;Richter et al 2003;Lehner et al 2009). We only, tentatively, identify one kinematic component between 30 and 230 km s −1 , viz.…”
Section: An Expanding Bubble Around R 136?mentioning
confidence: 90%
“…De Boer et al (1980 found UV absorption at 20 km s −1 (Galactic) and at 220, 250 and 290 km s −1 towards the LMC and proposed that the 220 km s −1 component might originate in coronal gas associated with the LMC. Intermediateand high-velocity clouds floating in the Galactic Halo have also been seen in front of the LMC at 60 and 120 km s −1 , interestingly also in H 2 absorption (Richter et al 1999;Richter et al 2003;Lehner et al 2009). We only, tentatively, identify one kinematic component between 30 and 230 km s −1 , viz.…”
Section: An Expanding Bubble Around R 136?mentioning
confidence: 90%
“…Methods for accurately deriving the density from multi-line observations have been successfully developed and applied e.g. by Schreyer et al (1997); Richter et al (2003); Sonnentrucker et al (2003). They are based on a combination of information from different species tracing a wide range of critical densities, but the accurate determination of ρ 0 still remains a challenging task.…”
Section: Derivation Of the Velocity Structure From Density-contaminatmentioning
confidence: 99%
“…From fine structure levels of C i, Welty (2007) discovered that the observed variations in Na i and Ca ii lines towards HD 219188 reflect the variation in the density and ionisation in the gas, and do not refer to high-density clumps. A different approach was used by Richter et al (2003a,b) who found, using the many absorption lines of molecular hydrogen in the Lyman and Werner bands, that the molecular gas in their studied lines of sight resides in compact filaments, which possibly correspond to the tiny-scale atomic structures in the diffuse ISM (Richter et al 2003a).…”
Section: Introductionmentioning
confidence: 99%